2018
DOI: 10.1021/acs.est.8b03869
|View full text |Cite
|
Sign up to set email alerts
|

Application of Environmental DNA Metabarcoding for Predicting Anthropogenic Pollution in Rivers

Abstract: Rivers are among the most threatened freshwater ecosystems, and anthropogenic activities are affecting both river structures and water quality. While assessing the organisms can provide a comprehensive measure of a river's ecological status, it is limited by the traditional morphotaxonomy-based biomonitoring. Recent advances in environmental DNA (eDNA) metabarcoding allow to identify prokaryotes and eukaryotes in one sequencing run, and could thus allow unprecedented resolution. Whether such eDNA-based data ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(97 citation statements)
references
References 74 publications
2
95
0
Order By: Relevance
“…If the aim is to maximize the phylogenetic diversity captured in a sample either a more conservative marker such as 18S can be appropriate (Deagle et al 2014, Bagley et al 2019), or -for metazoan taxa -it might be important to consider the use of multiple COI primers (Corse et al 2019, Hajibabaei et al 2019b) as with the more specific primer combination clearly a few macrozoobenthic taxa within Trichoptera, Mollusca, and Isopoda will be missed due to primer bias. It should be noted that also for broad eukaryotic markers the diversity of macrozoobenthic species can still be diluted and read numbers dominated by meiofaunal groups that life in the habitat (Rotifera, Copepoda, see Li et al 2018) but which are usually not part of the regulatory biomonitoring.…”
Section: Considerations For Macroinvertebrate Bioassessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…If the aim is to maximize the phylogenetic diversity captured in a sample either a more conservative marker such as 18S can be appropriate (Deagle et al 2014, Bagley et al 2019), or -for metazoan taxa -it might be important to consider the use of multiple COI primers (Corse et al 2019, Hajibabaei et al 2019b) as with the more specific primer combination clearly a few macrozoobenthic taxa within Trichoptera, Mollusca, and Isopoda will be missed due to primer bias. It should be noted that also for broad eukaryotic markers the diversity of macrozoobenthic species can still be diluted and read numbers dominated by meiofaunal groups that life in the habitat (Rotifera, Copepoda, see Li et al 2018) but which are usually not part of the regulatory biomonitoring.…”
Section: Considerations For Macroinvertebrate Bioassessmentmentioning
confidence: 99%
“…Thus, especially for indicator taxa, species or OTUs diversity was low. Li et al (2018) In the study by Hajibabaei et al (2019), which coined the term 'watered-down biodiversity', number of reads assigned to benthic invertebrates per eDNA sample was two orders of magnitude lower and diversity, measured as the number of exact sequence variants (ESVs) per sample, one order of magnitude lower compared to bulk samples. Pereira-da-Conceicoa et al (2019) showed that water samples from South African streams contained less than 10 % reads assigned to targeted macroinvertebrate taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Although eDNA metabarcoding assessments of alpha and beta diversity along environmental gradients are increasing (e.g. Hänfling et al, 2016; Olds et al, 2016; Kelly et al, 2016; Evans et al, 2017; Li et al, 2018a; Nakagawa et al, 2018), this tool is less commonly used for ecological hypothesis testing, such as the impact of environmental stressors (Li et al, 2018b; Macher et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…While these results, supported by a number of other studies, show that eDNA as currently sampled and analysed is an unlikely alternative to sampling whole organisms for detection of whole macroinvertebrate communities in the near term (Barnes & Turner, 2016; Blackman et al, 2019; Hajibabaei et al, 2019; Macher et al, 2018), the field is advancing at a rapid rate (Blackman et al, 2019; Deiner et al, 2017; Deiner, Mächler, et al, 2016; Li et al, 2018; Mächler et al, 2019; Majaneva et al, 2018). Our stringent approach using sequencing replicates should substantially reduce OTUs remaining which are a result of sequencing error but is also likely to have resulted in target taxa being lost from the eDNA samples at this sequencing depth.…”
Section: Discussionmentioning
confidence: 73%
“…However, as eDNA is free of the organism and can be transported in flowing waters (Deiner & Altermatt, 2014), these data are spatially complex (Deiner, Fronhofer, Mächler, Walser & Altermatt, 2016). While eDNA-based studies have been shown to successfully detect macroinvertebrate community richness (Deiner et al, 2017; Deiner, Walser, Mächler & Altermatt, 2016; Li et al, 2018; Mächler, Little, Wüthrich, Alther & Fronhofer, 2019) some studies have shown a much lower detection level of invertebrates when compared to morphological methods (Hajibabaei et al, 2019; Macher et al, 2018). These differences can be a result of several factors including DNA shedding rates, persistence and movement in the environment (Barnes & Turner, 2016), sampling, laboratory and bioinformatic biases as outlined in Blackman et al (2019).…”
Section: Introductionmentioning
confidence: 99%